Assembly Of Silver Nanocube Clusters And Tuning Of Surface Plasmon Resonances For Surface-Enhanced Raman Scattering - Lee, Seung Yong (2013)
To prepare surface-enhanced Raman scattering (SERS) substrate with metal nanoparticle clusters, various deposition methods were used: (1) vertical deposition (VertD), (2) electrophoretic deposition (EPD), and (3) block-copolymer templated deposition (BCPTD). The EPD is a high throughput process. Substrates for VertD can be reused. The BCPTD does not require the use of any lithography technique. By means of these three deposition methods, metal nanoparticles, including silver nanocubes and gold nanospheres, were positioned at pre-determined substrate sites. Various parameters, such as angle between cluster axis and laser polarization, gap size, number of cubes in clusters and cluster configurations, were investigated for their effect on SERS. Hexagonal arrays of gold nanoparticles with precisely controlled gap were investigated. The proximity of the plasmon resonance to the laser wavelength was correlated to the SERS enhancement. A database of SERS enhancement of silver nanocube clusters from monomers to tetramers was generated. The analysis of the structures and enhancements in this database reveals that clusters should be aligned with the laser polarization to achieve high SERS enhancement. Increasing cluster size from dimers to tetramers improves the reproducibility of enhancement factor values. Non face-to-face clusters are better in SERS enhancement than face-to-face clusters. Sharp corners at the junctions are essential for high SERS enhancement.